Komunikasi Guru dengan Siswa dalam Adaptasi Kegiatan Belajar Mengajar Online di Masa Pandemi Covid-19 - Enggar Danurdoro; Wulan Tri Gartanti (UNISBA Press, 2022)
Abstract.These Days, communication is increasingly made easier by the existence of technology or digital media to communicate, call it mobile phones, radios, to laptops or computers. We don't need to worry about differences in distance or time to communicate, because with the media mentioned above, we can communicate anytime and anywhere we want to start communicating with the people we want to go to. This research is entitled